EFEKTIVITAS ORGANISASI KELOMPOK TANI DI DESA SILANCA KECAMATAN LAGE KABUPATEN POSO - Andika Nugra Deo Bermuli; Nawawi Natsir; Ani Susanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Andika Nugra Deo Bermuli, B10222102. Supervisors Mr. Nawawi Nasir and Mrs. Ani Susanti with thesis title The Effectiveness of Farmer Group Organizations in Silanca Village, Lage District, Poso Regency. In general, this research aims to find out the effectiveness of farmer group organizations in Silanca Village, Lage District, Poso Regency. In writing, this research uses a descriptive research method, namely research carried out within certain rules that exist in real life which systematically and accurately describe and explain the situation of the Organizational Effectiveness of Farmer Groups in Silanca Village. The basis of the research used is qualitative research. The theory used in this research is the theory of Richard M. Steers which includes three indicators, namely Goal Achievement, Integration and Adaptation. From the research results it is known that based on the Goal Achievement indicator. Based on the Integration indicators, seen from the aspects: First, Coordination. From the research results it is known that from the aspect of internal and external coordination it has not been effective, both socialization has been effective. Based on indicators, adaptation has not yet run optimally.